Student Leadership on Community Empowerment: Study on Zero Waste Program in Lamongan, East Java. - Haryo Kunto Wibisono; Noviyanti Noviyanti; Yuni Lestari; Weni Rosdiana; Agus Prastyawan (Universitas Sebelas Maret, 2024)
This article explores the role of students as leaders in activities related to public interests and problems, especially issues of community empowerment in Indonesia. The community empowerment project is Zero Waste Village Project in Kediren, Lamongan, East Java. Based on qualitative methods and interview techniques and non-participatory observation of a group of students involved in community empowerment activities, we underline the role of students as leaders through the criteria of personality, ability, behavior, relationships, and process. The results of the research show that students' leadership attitudes are demonstrated in their personalities, which can be seen in their sociability and care to society as well as the challenges and opportunities that exist. Ability is seen in the application of project organizing skills as well as students' knowledge about waste problems. This knowledge can also be seen as the power that leaders use to make changes, as well as relating to the relationship between the leader and the people they lead. Behavior can be seen in increasing understanding and motivation, providing facilities for residents, activating existing resources in the village, as well as implementing cooperation and coordination. The transformational process can be seen in this series of activities, in which students, as initiators and implementers, have raised citizen awareness, shared knowledge, and carried out solution activities, as well as encouraged citizens to take part in projects actively.